The role of policy in the conservation and extended use of underutilized plant species: a cross-national policy analysis - Chishakwe, N.E.; Genetic Resources Policy Initiative; Global Facilitation Unit for Underutilized Species (2008)
”The role of policy in the conservation and extended use of underutilized plant species: a cross-national policy analysis” was prepared by the Global Facilitation Unit for Underutilized Species (GFU), in cooperation with the Genetic Resources Policy Initiative (GRPI). This report, an effort of the GFU to set the scene and provide an instrument for policy and decision makers, presents a cross-national analysis of policies that hinder or promote the conservation and use of underutilized species. It is based on national policy studies undertaken in Ghana, Jordan, Nepal, Papua New Guinea, Peru, Uzbekistan, Vietnam and Zambia. These studies are published on the GFU web site and links to each study are included in the References section of this report. A separate publication ”An overview of the international regulatory frameworks that influence the conservation and use of underutilized plant species” is available in hardcopy or on line and analyzes some of the important international policy instruments that affect the conservation and extended use of underutilized plant species.